Job Insecurity and Mental Well-Being in Finland, Norway, and Sweden - Vulkan, Patrik; Saloniemi, Antti; Svalund, Jørgen; Väisänen, Anna (Nordic Journal of Working Life Studies, 2015)
This article describes how the flexicurity arrangement of low job security, high employment security, and good income security advocated by various authors affects the mental well-being of employees. Data are derived from a survey carried out in 2010–2011 among employees in Finland, Norway, and Sweden. The main findings are that all three forms of cognitive security (the perceived risk) have an independent effect on mental well-being and that the worry of insecurity (the affective component) mediates the relationship with mental well-being. The interaction effects show that high levels of employment security can alleviate the detrimental effects of job insecurity on mental well-being. No similar interaction effect was found with job insecurity and income security. The results are discussed in relation to the institutional arrangements of the Nordic countries’ welfare states, concluding that the high employment security needed for a successful flexicurity arrangement requires either low levels of unemployment or effective and extensive active labor market programs. Flexicurity is thus susceptible to economic turmoil and requires further labor market investments, even in the Nordic countries.